1995
DOI: 10.1080/01688639508405148
|View full text |Cite
|
Sign up to set email alerts
|

Is there a sex difference in human laterality? II. An exhaustive survey of visual laterality studies from six neuropsychology journals

Abstract: The contents of six neuropsychology journals (98 volumes, 368 issues) were screened to identify visual half-field (VHF) experiments. Of the 516 experiments identified, 42% provided information about sex differences. Sixty-eight experiments yielded a total of 92 sex differences, 23 of which met stringent criteria for sex differences in laterality. Of the 20 sex differences satisfying stringent criteria and lending themselves to interpretation in terms of the differential lateralization hypothesis, 17 supported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
1
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(52 citation statements)
references
References 61 publications
5
45
1
1
Order By: Relevance
“…These sex-related differences in spatial attention and the effect of sex demonstrated here are possibly of similar origin. It has been proposed that such sex differences could be associated with the stronger brain asymmetry in men, resulting in a more effective use of the right hemisphere, which is specialized for spatial functions (Halpern, 1996;Hausmann and Güntürkün, 1999;Hiscock et al, 1995;McGlone, 1980). This view predicts a sex-specific asymmetry in performance, which was not established by the present analyses.…”
Section: Sex Differencescontrasting
confidence: 63%
“…These sex-related differences in spatial attention and the effect of sex demonstrated here are possibly of similar origin. It has been proposed that such sex differences could be associated with the stronger brain asymmetry in men, resulting in a more effective use of the right hemisphere, which is specialized for spatial functions (Halpern, 1996;Hausmann and Güntürkün, 1999;Hiscock et al, 1995;McGlone, 1980). This view predicts a sex-specific asymmetry in performance, which was not established by the present analyses.…”
Section: Sex Differencescontrasting
confidence: 63%
“…For example, multiple findings from studies indicated that women are less lateralised than man fMRI [21], dichotic listening [11] and visual laterality when processing language [11,17]. Because this could studies [12] suggest stronger lateralisation of language explain the temporal advantage of women in our data, all functions to the left hemisphere in males, whereas lansubjects were reinvited to participate in a dichotic listening guage functions in females tend to be organised more experiment. Fifty-five of the 64 ERP participants returned bilaterally.…”
Section: Dichotic Listeningmentioning
confidence: 68%
“…Borod et al, 1983;Killgore & Yurgelun-Todd, 2001). A systematic review on VHF studies by Hiscock et al, (1995) reported that 17 out of 92 relevant outcomes show reduced FCAs in females compared to males. An observation that is in line with other reviews and meta-analyses (e.g.…”
Section: Discussionmentioning
confidence: 99%